2020
DOI: 10.1029/2020tc006198
|View full text |Cite
|
Sign up to set email alerts
|

Aptian Flysch in Central Tibet: Constraints on the Timing of Closure of the Bangong‐Nujiang Tethyan Ocean

Abstract: The timing of the closure of the Bangong-Nujiang Tethyan Ocean is highly controversial. An important reason for this is that the sedimentological work within the Bangong-Nujiang suture zone is not sufficient. In this study, based on the U-Pb zircon dating of turbiditic sandstone and tuff interlayers, we determine the existence of Aptian flysch (ca. 126-113 Ma) in the middle and western segments of the Bangong-Nujiang suture zone. Further analysis shows that the Aptian flysch was deposited in a trench environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 87 publications
(248 reference statements)
0
8
0
Order By: Relevance
“…Marine sediment rocks Existence of oceanic basin (Baxter et al, 2009;Luo et al, 2020;Zhang et al, 2014Zhang et al, , 2012.…”
Section: Unconformity Between the Shamuluo Formation And Early Jurassmentioning
confidence: 99%
See 3 more Smart Citations
“…Marine sediment rocks Existence of oceanic basin (Baxter et al, 2009;Luo et al, 2020;Zhang et al, 2014Zhang et al, , 2012.…”
Section: Unconformity Between the Shamuluo Formation And Early Jurassmentioning
confidence: 99%
“…This view is consistent with recent high-quality paleomagnetic data obtained from western Tibet and covering the study area, which reveal: (a) a 2,600 ± 710 km and ∼825 ± 600 km width for the western Meso-Tethys Ocean during the Late Jurassic (∼160 Ma) and late Early Cretaceous (∼120-115 Ma), respectively (Cao et al, 2019(Cao et al, , 2020; and (b) the Lhasa Terrane drifted ∼8.5° northward from 123 ± 9 Ma to 97 ± 7 Ma and paleolatitudinally overlapped with the Qiangtang Terrane after ∼111-103 Ma (Chen et al, 2017;Meng et al, 2017). In addition, a recent integrated study of geological, sedimentological, and geochronological evidence has shown that Aptian deep-water deposits in the western BNSZ are analogous to those deposited in a trench basin rather than a peripheral foreland basin (Luo et al, 2020).…”
Section: Evidence For Early Cretaceous Ophiolites Within the Bnszmentioning
confidence: 99%
See 2 more Smart Citations
“…The Sm/Yb ratios can be used to distinguish between the partial melting of garnetand spinel-lherzolite sources, because magmas generated from a spinellherzolite source has nearly constant Sm/Yb ratios, where magmas from a garnet-lherzolite source will exhibit increased Sm/Yb ratios compared with the mantle source (Aldanmaz et al, 2000). The Bilong Co basalts have Sm/Yb ratios of 3.31-3.53, higher than those of the mantle array Qin, et al, 2014;Luo et al, 2020;Ma et al, 2017;Shi et al, 2020;G. Y.…”
Section: The Nature Of the Mantle Sourcementioning
confidence: 99%